Lunar and Solar Geomagnetic Tides in the Geomagnetic Equatorial Region- II Geomagnetic Tidal Variations at Alibag Equinoxes (MAUSAM, 1962)
The lunar and solar geomagnetic tides at Alibag are determined- by the fixed age method following the Chapman-Miller technique, for the three seasons-December solstice, equinoxes and summer solstice. The seasonal variation in the amplitudes and phases of L(H) are compared with similar results for Kodaikanal, Season Hnancayo and Ibadan, Confirmation has been obtained for an earlier suggestion of the author that the southern hemispheric currents in ionosphere which cause L variations extend upto 10oN geomagnetic latitude in December season. The nature of the seasonal variations of L(H) at Alibag is the same as that at Ibadan, and different from what is obtaining at Kodaikanal and Huancayo.